Relevance between transfer pricing and taxpayer compliance and marketing accounting management efficiency - Hendriarto, Prasetyono (Linguistics and Culture Review, 2021)
Transfer pricing is crucial because every company certainly has a goal, namely to get profits through minimal expenses, perhaps reducing tax overpayments to become one of the most efficient and productive companies. To prove this hypothesis, this study has conducted a series of evidence through many special scientific publications that discuss transfer pricing of tax obligations and the accounting efficiency of corporate management. The data will certainly not be helpful and answer questions without first going through a comprehensive review process which is carried out, among others, through a phenomenological approach in which there is a critical coding and evaluation system so that we can obtain valid and detailed data to answer the last study question. Based on the data exposure supported by the evidence of field findings, we can conclude that this transfer pricing activity is indeed a part of accounting and taxation practices which allows transactions both internally within the company and with other partner companies, which of course operate in terms of 1 commitment in terms of goals and objectives. Ownership of the company and transfer pricing is also a mechanism for companies to achieve significant profits by reducing tax management rights and avoiding risk loss.